Some influences on the autonomy of Chilean journalists: an update of previous research - Greene González, Francisca (2017)
In them, it was found that there were influences of its editors, in addition to the pressures exerted by the company and the sponsors. The aim of this paper is to analyze some of the influences of journalists, 15 years after the beginning of this research. It is intended to evaluate the conclusions of previous research and add another factor: the effect of social networks as a new element of pressure. In-depth interviews were conducted with eight journalists who worked as reporters on various national media. The elected journalists were young, precisely to evaluate new opinions regarding perceived autonomy. It was concluded that, for half of the interviewed journalists, the economic pressures of the owners of the company lack autonomy; Most do not feel pressured by their editors and social networks mean, for half the interviewees, a factor to take into account in their publications.